Quantum and semiclassical polarization correlations - Banaszek, K; Demkowicz-Dobrzanski, R; Karpinski, M; Migdal, P; Radzewicz, C (2010)
We analyze the strength of polarization correlations between two light beams that can be achieved in the semiclassical regime using statistical mixtures of coherent states and binary on/off detectors. Under certain symmetry assumptions, the visibility of polarization correlations is shown to be bounded by frac(1, 3), which is in a striking contrast with perfect 100% correlations exhibited by photon pairs prepared in the singlet state. The semiclassical limit is demonstrated in a measurement performed on a pair of laser beams undergoing correlated depolarization. This result illustrates the dramatic difference between predictions of quantum mechanics and the semiclassical theory of electromagnetic radiation for the polarization degree of freedom. © 2009 Elsevier B.V. All rights reserved.